1989
DOI: 10.1071/bt9890103
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Function in the Mimosoid Legume Acacia retinodes: Ultrastructural and Cytochemical Characteristics of Stigma Receptivity

Abstract: The stigma of Acacia retinodes is receptive from the moment the flower opens (female phase). Receptivity, assessed in terms of pod set, is highest at flower opening, and lowest the following day (male phase). Stigma receptivity is associated with the acquisition of a heterogeneous stigma exudate, the components of which are secreted sequentially during differentiation. Cytochemical probes have tentatively identified the principal components as unsaturated and saturated lipids, free fatty acids, flavonoid aglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…This kind of droplet has not yet been found in other solid styles. Stigma cells in Lycopersicurn pervianurn (Dumas et al 1978) and Acacia retinodes (Knox et al 1989) contain lipid droplets that are quite similar to those observed in Japanese pear. Dumas et al (1978) reported a relationship between the occurrence of this droplet and rough ER and Golgi bodies.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This kind of droplet has not yet been found in other solid styles. Stigma cells in Lycopersicurn pervianurn (Dumas et al 1978) and Acacia retinodes (Knox et al 1989) contain lipid droplets that are quite similar to those observed in Japanese pear. Dumas et al (1978) reported a relationship between the occurrence of this droplet and rough ER and Golgi bodies.…”
Section: Discussionsupporting
confidence: 49%
“…Their results on the incorporation of labeled myo-inositol-2-3H with the lipid body suggest that parts of some lipid bodies include carbohydrate materials and that the conversion to the polysaccharide particles takes place within the lipid bodies. Knox et al (1989) revealed that the surface of the lipid droplet in Acacia stigma is a carbohydrate with vicinal glycol groups that react to the periodic acid thiocarbohydrazide silver proteinate. Thus, these droplets were considered to be heterogenic droplets: hydrophobic within the droplets, and hydrophilic at their surface.…”
Section: Discussionmentioning
confidence: 99%
“…The prior or simultaneous deposition of self‐, incompatible or related pollen by pollinators may interfere with the ability of plants to use available cross‐pollen, resulting in reduced fruit and seed set. Self‐pollen grains may cause clogging or blocking of stigmatic surfaces, preventing cross‐pollen from adhering and germinating (especially considering the small size of stigmatic papillae in Acacia ; Kenrick & Knox, , ; Knox et al ., ; Moncur, Moran & Grant, ) or reducing cross‐pollen tube development (Ramsey & Vaughton, ; Quesada‐Aguilar, Kalisz & Ashman, ). However, the massive production of flowers by these Acacia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Between the microspore release stage and the young microspore stage, the close association between the SER and the plastid gives rise to some lipid globules, showing the involvement of this process in pollenkitt formation. These globules exhibit intense reaction to the PATAg test, indicating a higher degree of unsaturation (Knox et al 1989). This might further indicate that plastid/SER interaction consists of, at least, lipid desaturation.…”
Section: Discussionmentioning
confidence: 99%